How do I chase away this man? From Bosco to Dismas, unpacking the situated knowledges of MTN Uganda’s adverts - Nasaba, Robert Madoi (Informa UK Limited, 2021)
Much of the appeal of advertisements or adverts derives from a capacity to satisfy a primordial wish for pleasurable looking. An advert essentially sets out to impress on its audience a sign with easily readable mythic meaning. The unconscious of society, however, structures materiality of adverts in such a way that recognition could quite easily be overlaid with misrecognition. This paper uses semiotics to discover where and how the visual presence of adverts works against their intended hegemonic positions. Drawing upon a poststructuralist theoretical framework, the paper’s findings depart from claims to comprehensiveness and instead show a deferral of meaning. They also embrace plurality whilst questioning the validity of authorial authority. Results indicate that the alienated subject – MTN Uganda’s TV adverts – gave rise to other identification tags because its target audience knowingly and willingly wanted to have agency over their stories. The counternarrative that this paper unearths in part owes its existence to social media’s calling card, social endorsements or affordances, which trigger several decision heuristics. The poststructuralist situated knowledges in this case open themselves for new, unthought-of, and, perhaps, unexpected forms of knowledge production, unfolding from interrelated material-semiotic nodes.